The role of causality and conceptual coherence in assessments of similarity - Spiteri, Louise F. (2021)
Conceptual coherence, which refers to concepts whose contents make sense to the perceiver, has been associated traditionally with the notion of similarity, that is, objects, events, or entities form a concept because they are similar to one another. An examination of traditional similarity-based concept theories suggests that they do not provide an adequate account for conceptual coherence. Library and Information Science needs to explore knowledge-based approaches to concept formation, which suggest that one’s knowledge of a concept includes not just a representation of its features but also an explicit representation of the causal mechanisms that people believe link those features to form a coherent whole.